تأثير تمرينات بصريه مهاريه في تطوير بعض القدرات العقلية وتعلم مهارة الإعداد بالكرة الطائرة - عبدالله, ذيان عبدالله نوري; لفتة, عامر راشد شيال (Sulaimani Journal for Humanities, 2018)
The study aimed to prepare visual skill exercises and find out the effect of this exercises on the development of some mental capacities and setting skill learning in Volleyball. The researchers assumed that the Visual skill exercises have a significant effect on the development of some mental capacities and setting skill learning in volleyball. The study included theoretical and similar studies of the visual exercise, mental capacities and basic skills in volleyball. Pretest-posttest experimental design was adopted in this study. The participants were 30 students selected purposely from the second stage in the Faculty of Physical Education and Sport Sciences / University of Wasit, divided randomly into two groups (experimental and control). Methods and process of this study were identified. In addition, SPSS were used to analyze data.